Accuracy of polyether and vinylpolysiloxane impressions when using different types of 3D-printed impression trays: an in vitro study - Rues, Stefan; Depré, David; Stober, Thomas; Rammelsberg, Peter; Zenthöfer, Andreas (Clinical oral investigations, 2024)
To investigate dimensional accuracy of polyether (PE) and vinylpolysiloxane (VPS) impressions taken with manually fabricated and 3D-printed trays.